Innovative voucher as a prospect tool for grant funding - V. A. Barinova; V. A. Eremkin (Ekonomika Nauki, 2015)
The article aims to explore innovative international practice for advancing the mechanisms of distributing grant funding. Authors analyze a practical case study of successful implementation of innovative vouchers overseas, and draw parallels with regard to already formed institutes in Russia, corresponding with foreign in terms of their functional. Possible mechanisms for implementing successful foreign practices of utilizing innovative vouchers in Russia were studied in this article. On the basis of conducted analysis authors evaluate perspectives of implementing the suggested scheme in Russia.